Targeted defect analysis in VCSEL oxide windows using 3D slice and view. (11th May 2021) - Sun, X; Rickard, W D A; Ironside, C N; Kostakis, I; Missous, M; Powell, D; Anjomshoaa, A; Meredith, W
Abstract: We report on high resolution analysis of vertical cavity surface emitting lasers (VCSELs) to detect and assess defects in sub-surface layers. We employ a focussed ion beam scanning electron microscope (FIB-SEM) to sputter and image successive cross sections (slice and view technique) in order to produce a 3D reconstruction of the oxide aperture region. High resolution images and measurements of the multilayers and oxide apertures of VCSEL devices were obtained. The process took ∼2.5 h and produced over 270 slice SEM images for a device volume of approximately 13.2 × 16.0 × 13.8 μ m 3, with a voxel size of 50 nm. On-wafer, single mode VCSEL devices with high and low output powers were analysed to compare their oxide apertures and distributed Bragg reflector (DBR) layer structures. It was found that the low output power VCSEL had DBR layer defects and a 41.8% reduction of effective oxide aperture area, explaining the lower power obtained. The results provide evidence that oxide aperture area and structural defects are major factors that affect the optical output power of VCSEL devices. Outcomes in this work show FIB-SEM slice and view is a valuable method for 3D reconstruction of VCSEL devices, which enables top view, cross-sectional view and angled view of the whole device region as well as designated structures such as oxide aperture or structural defects in various layers. This work demonstrates a promising technique with high resolution (50 nm) 3D imaging for analysis of complex semiconductor devices.